Prevalence of Dental Caries, Oral Hygiene Status, and Associated Risk Factors Among Schoolgoing Children of Rajshahi District in Bangladesh (TAJ: Journal of Teachers Association, 2022)
Introduction: Dental caries is one of the most prevalent and chronic oral diseases, particularly in childhood, associated with multifactorial causation.Objective: The study aimed to determine the prevalence of dental caries, oral hygiene status, and associated risk factors among school-going children of Rajshahi District in Bangladesh.  Methods: This cross-sectional design type of descriptive study was carried out among primary school-going children of 5-13 years of age in the Rajshahi district. The sample size was 2000, and that was selected purposively. Data were collected through a partially structured questionnaire. Descriptive variables were explained with mean and standard deviation. The Chi-square test was applied to see the relationship with qualitative variables. Statistical significance was found by applying relevant statistical tests at an appropriate probability level (p